Rethinking identity through Hindu spirituality in K.S Maniam's novels - Awang, Mohammad Ewan (2016)
In one of his essays, K.S Maniam, a Malaysian Literature in English author states that his literary works “attempt to bring the precision of the English language to the versatility and depth of Hindu mythology and spirituality” (“Fiction into Fact” 264). Despite his assertion, the role of Hindu spirituality in his works especially in relation to the Malaysian Indian identity construction remains little studied. Past studies tend to approach identity in Maniam’s works using the post-colonial theory and focus mainly on the politics of identity construction. Hitherto, the discussion of identity in Maniam’s works is limited to the political and sociological realms. Therefore, my thesis attempts to go beyond these realms by suggesting an alternative discourse of identity through spirituality. My central argument is that spirituality plays a significant role in identity construction in K.S Maniam’s novels. To address this, I employ Advaita Vedanta, an Indian philosophy as a theoretical framework in order to highlight an alternative rendering of identity in Maniam’s novels. Advaita Vedanta’s conception of identity rests on monistic and undifferentiated whole called Atman (True Self) which can only be achieved when a person transcends subject-object dichotomy. Advaita Vedanta’s accentuation of “non-duality” is revolutionary as it restructures the concepts relevant to identity such as one’s sense of selfhood, one’s relationship with the world, and one’s perception and experience of reality. I analyse all of Maniam’s novels which are The Return (1981), In a Far Country (1993), and Between Lives (2003) and show how his works reflect the philosophy of Advaita Vedanta. Maniam incorporates this Indian philosophy into his works by means of literary motifs such as self-reflexivity, rites-ofpassages, rituals, disruptions of temporal/spatial linearity, and mystical experiences. These motifs highlight how spirituality informs identity construction in Maniam’s novels. My thesis shows that spirituality in KS Maniam’s novels is transformative in three ways. Firstly, spirituality revolutionizes the way the characters perceive and comprehend the notion of “self” and “reality”. Secondly, spirituality depathologizes the characters’ existential crises. And thirdly, spirituality renews human relations as it emphasizes the importance of upholding moral and ethical duties, compassion, and empathy. To conclude this study, I reiterate that spirituality provides a more paradigmatic discourse of identity and at the same time allows K.S Maniam to articulate his creative and intellectual voice as a Malaysian Indian author.